Lessons Learnt from Imaging Review of Interval Breast Cancers in a Single Center in the UK National Breast Screening Program - Jia Mang Lee; Palida Jantarang; Bhavani Rengabashyam (Indian Journal of Radiology and Imaging, 2024)
False-negative mammograms are a part of any screening program and the National Breast Screening Program in the United Kingdom is no exception. Every year, 2.5 million women have screening mammograms in the United Kingdom. Around 8 per 1,000 women screened are diagnosed with a breast cancer and 3 per 1,000 women will present with an interval breast cancer following a negative screening mammogram and before their next mammogram.